Ice-sheet melt drove methane emissions in the Arctic during the last two interglacials - Dessandier, Pierre-Antoine; Knies, Jochen; Plaza-Faverola, Andreia; Labrousse, C.; Renoult, M.; Panieri, Giuliana (Geology, 2021)
Circum-Arctic glacial ice is melting in an unprecedented mode, and release of currently trapped geological methane may act as a positive feedback on ice-sheet retreat during global warming. Evidence for methane release during the penultimate (Eemian, ca. 125 ka) interglacial, a period with less glacial sea ice and higher temperatures than today, is currently absent. Here, we argue that based on foraminiferal isotope studies on drill holes from offshore Svalbard, Norway, methane leakage occurred upon the abrupt Eurasian ice-sheet wastage during terminations of the last (Weichselian) and penultimate (Saalian) glaciations. Progressive increase of methane emissions seems to be first recorded by depleted benthic foraminiferal δ13C. This is quickly followed by the precipitation of methane-derived authigenic carbonate as overgrowth inside and outside foraminiferal shells, characterized by heavy δ18O and depleted δ13C of both benthic and planktonic foraminifera. The similarities between the events observed over both terminations advocate for a common driver for the episodic release of geological methane stocks. Our favored model is recurrent leakage of shallow gas reservoirs below the gas hydrate stability zone along the margin of western Svalbard that can be reactivated upon initial instability of the grounded, marine-based ice sheets. Analogous to this model, with the current acceleration of the Greenland ice melt, instabilities of existing methane reservoirs below and nearby the ice sheet are likely.